2007
DOI: 10.1007/s10708-007-9095-7
|View full text |Cite
|
Sign up to set email alerts
|

Military pollution and natural purity: seeing nature and knowing contamination in Vieques, Puerto Rico

Abstract: Military activities have produced contaminated environments at many sites around the world. This contamination and the associated health risks play a large role in how these places can be redeveloped after military use. In this essay we focus on the island of Vieques, Puerto Rico which was used as a bombing range by the US military for six decades until 2003. We examine the ways different groups of people perceive this formerly militarized landscape and the ways that these perceptions legitimatize certain rede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…On the one hand, geographic research has documented how the rise of an industrial militarism, as exhibited by the use of landmines and cluster bombs, chemical weapons, and depleted uranium, has left a distinct -and lethal -imprint on the landscape (Wilson, 1988;Hupy, 2006;Davis et al, 2007;Hupy and Schaetzl, 2008;Tyner, 2010;Hupy and Koehler, 2012). Much of this work has adopted a critical perspective, noting that the military detritus of warfare continues to pose health risk to both people and the environment years after the violence has supposedly ended.…”
Section: Nature and Warmentioning
confidence: 99%
“…On the one hand, geographic research has documented how the rise of an industrial militarism, as exhibited by the use of landmines and cluster bombs, chemical weapons, and depleted uranium, has left a distinct -and lethal -imprint on the landscape (Wilson, 1988;Hupy, 2006;Davis et al, 2007;Hupy and Schaetzl, 2008;Tyner, 2010;Hupy and Koehler, 2012). Much of this work has adopted a critical perspective, noting that the military detritus of warfare continues to pose health risk to both people and the environment years after the violence has supposedly ended.…”
Section: Nature and Warmentioning
confidence: 99%
“…The military forces of many nation-states, particularly those of advanced capitalist economies, have increasingly been held to account by national governments and by pressure groups and the environmental lobby over environmental impacts, and it is worth noting how external critique has often prompted remedial action. However, and as a number of commentators have noted, the levels of environmental destruction and contamination produced as a consequence of military activities have been of sufficient severity or extent as to merit explanatory strategies and explanations rife with political intent concerning armed forces' self-image (see Davis, 2005Davis, , 2007Davis, Hayes-Conroy, & Jones, 2007;Havlick, 2007Havlick, , 2011. Critiques have moved beyond the simple idea of a 'greenwash' to focus on the complex interplay between defence objectives around the use of landscapes, and defence objectives around the presentation for public consumption of explanations around the uses of such landscapes.…”
Section: The Variety Of Military Landscapesmentioning
confidence: 99%
“…Public data reveal that environmentally hazardous military activities in USA have generated on average a ton of toxic waste per minute during the last eight years, making them the largest source of pollution in the USA [1]. The U.S. Army Corps of Engineers has stored waste coming from the production of nerve gas and pesticides during the Second World War and the Vietnam War era at the Rocky Mountain Arsenal in Denver (Colorado).…”
Section: Environmental Pollution By Military Activitiesmentioning
confidence: 99%
“…Government health data indicated that risk of mortality from cancer was 1.39 times higher in Vieques than on the main island (Puerto Rico). Cancer risk in Vieques was found to increase since the early 70s [1]. …”
Section: Environmental Pollution By Military Activitiesmentioning
confidence: 99%